PELATIHAN PEMBUATAN PUPUK ORGANIK YANG BERKUALITAS DARI LIMBAH PETERNAKAN SAPI DAN BABI DI DESA MARGA DAUHPURI, KECAMATAN MARGA, KABUPATEN TABANAN - MEGA I M; I W.DANA ATMAJA; ID .OKA WIDYARSHANA; I A. SUTY ADNYANI; I N. DIBIA; DWI PUTRA DARMAWAN (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2009)
ABSTRACT The training programme of making the qualities organic fertilizers derived from waste livestock cattle and pig were conducted at Marga Dauhpuri village, Marga District, Regency of Tabanan, from June until October 2008. The purpose of this programme was improving society skill on making organic fertilizers.The methods of programme were : !) giving counseling to livestock farmers who merged into group of Livestock Sari Buana about : environmental contamination problem by waste of livestock of cattle and pig, and way of the settlement of disposal 2) Training of making organic fertilizers ( compost) having quality from waste of ranch of cattle and pig. The results of devotion activity to this society were 1) can improve the society awareness specially group of farmer of livestock Sari Buana about : a) livestock waste deriving from cattle and pig become the economic valuable substance in order not to spoil environment b) Dirt of pig and cattle become the organic manure (compost) which is good for crop 2) Can improve skilled in making organic fertilizers ( compost) having quality from dirt of cattle and pig 3) The yielding of certifiable compost with the characteristic : dark brown color, granulous refine, not smell and content of element nutrient namely : C-Organic ( 3.04 %); N-Total ( 0.41 %), available-P ( 20.56 ppm), available-K ( 842.31 ppm), C / N ( 7.41) for the compost of cattle dirt, and C-Organic ( 3.70 %); N-Total ( 0.16 %), available-P ( 35.91ppm), available-K ( 2517.10 ppm), C / N (23.13) for the compost of pig dirt